2020
DOI: 10.1097/mpg.0000000000002821
|View full text |Cite
|
Sign up to set email alerts
|

Two‐hour Observation After Liver Biopsy in Children

Abstract: Objective: Following percutaneous liver biopsy performed at our institution on an outpatient basis, children traditionally were observed for 4 hours then discharged after verifying a stable hematocrit level. In June 2015, we adopted a quality improvement project with shorter 2-hour observation for patients with no known risks and the hematocrit test was abandoned. The purpose of this study is to evaluate the clinical and economic outcomes of early discharge of children following liver b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…A reduced recovery time will help to decrease department cost and cost for the patient though there are not many studies performed to prove this. Alomari et al (2020) showed a 35% cost savings per procedure with a postprocedural observation time of 2 hours due to reduced facility fee cost and decrease in nursing staff utilization resulting in more efficient use of facility, space, and nursing staff. Nurses are an integral part of the liver biopsy process from the preprocedure interview, pre- and postprocedure assessments, along with their education and experience.…”
Section: Discussionmentioning
confidence: 99%
“…A reduced recovery time will help to decrease department cost and cost for the patient though there are not many studies performed to prove this. Alomari et al (2020) showed a 35% cost savings per procedure with a postprocedural observation time of 2 hours due to reduced facility fee cost and decrease in nursing staff utilization resulting in more efficient use of facility, space, and nursing staff. Nurses are an integral part of the liver biopsy process from the preprocedure interview, pre- and postprocedure assessments, along with their education and experience.…”
Section: Discussionmentioning
confidence: 99%